Analisis Pemilikan Pasaran Eksport Negara-Negara OIC 1996-2005 - Mohd Hussin, M. Y.; Muhammad, F.; Habidin, N. F.; Salleh, M. I. (Universiti Sains Islam Malaysia, 2024)
This study analyzes the export market share of selected OIC countries from the year 1996 until 2005. In this research, the market is divided into three categories which are import market of the world, import market among OIC countries and import market of non OIC membership countries. Findings reveal that export market share of the OIC countries is increasing each year in the three markets under study with the exception in 1998. Based on market share, Malaysia and Saudi Arabia have bigger share value of export market compared to other OIC countries.